Determinants of Smallholders’ Beef Cattle Market Participation: In Selected Districts of West Shewa Zone, Ethiopia - Fikiru Temesgen; Dabesa Wegari (International Journal of Supply Chain Management, 2021)
The study was aimed at analyzing determinants of smallholders’ beef cattle market participation and quantity supplied to the market in Toke Kutaye and Bako Tibe Districts, West Shewa Zone, Oromia National Regional State, Ethiopia. The primary data for this study were collected from 376 sampled household producers by using interview schedule, site visit and personal observation. Data analysis was made using descriptive and inferential statistics and heckman two-step selection model. The results of the heckman two-step selection model indicated that beef cattle market participation and quantity supplied to the market is significantly determined by education level, household size, using veterinary services, grazing land owned, selling price of cattle, frequency of farmer gets market information, body condition of cattle and total number of cattle owned. It was concluded that there is poor market information and infrastructure, lack of access to services and weak linkage of producers with next actors. Access to market information and infrastructure and veterinary services improves market participation and supplying of cattle. Therefore, the required recommendations were improving farmers’ access to market information and infrastructure by improving linkages between the producers and service provider institutions, creating strong horizontal and vertical linkage between the farmers and other chain actors and enabling them to produce market oriented products and supplying to the market.